Persepsi Mahasiswa pada Pelaksanaan Program Kampus Mengajar di Universitas Islam Riau - Fatikhah, Nur; Amalia, Rizka; Muhayatun, Siti; Mukhlis, Muhammad (UIR Press, 2023)
Seeing the number of enthusiasts in the teaching campus program that is followed by students. So, researchers feel interested in examining the impact or influence of the campus teaching program through students who have participated in the program. So the title of this study is